Effect of inoculum form of exserohilum longirostratum on disease development - Mohammad Hailmi, Sajili; Kadir, J. (2013)
Two types of inoculum (spore suspension and mycelium suspension) of Exserohilum longirostratum were tested on barnyard grass (Echinochloa cruss-galli) to compare the efficacy of mycelial base-suspension and spore-base suspension as two different substrata on the disease severity. The best result of both suspensions was selected to investigate an easy, rapid and inexpensive treatment as inoculum type used. The results showed that a concentration of 105 spores/mL in 30% oil of E. longirostratum incited higher disease severity compared to 107 and 108 spores/mL. However, no significant difference was observed between treatments of 105 and 106 spores/mL. In a mycelium base study, 20% oil of 5 day-old mycelial-shake cultures presented a better result compared to 3 day-old and 7 day-old cultures. Moreover, 1:5 ratio of 5 day-old mycelium suspension showed significantly higher disease severity than ratios of 1:3, 1:4 and 1:6.